The impact of applying the principles of Proverbs 3:1-8 on relationship harmony in Christian families - Henry Ekacahya Putra (KAMASEAN: Jurnal Teologi Kristen, 2025)
This study examines the impact of implementing the principles of Proverbs 3:1–8 on the development of harmonious relationships within Christian families. Employing a qualitative case study approach supported by descriptive and comparative quantitative analysis, the research involved 15 Christian families who consistently practiced these biblical principles over twelve months. Data were collected through structured interviews, family harmony surveys, observational logs, and self-assessment questionnaires, enabling triangulation of spiritual practices and measurable relational outcomes. The findings reveal six major transformative impacts supported by quantitative indicators. The application of the principle of obedience (Prov 3:1–2), the practice of love and faithfulness (Prov 3:3–4), the reliance on God in decision-making (Prov 3:5–6), the cultivation of spiritual humility (Prov 3:7–8), also the practical embodiment, established a stable family value system, reflected in the adoption of daily family Bible reading rituals by 86% of participants, which corresponded to a 78% increase in perceived family cohesiveness. Finally, a holistic transformation was observed across three key dimensions: a shift from a busyness-oriented lifestyle to a God-centered family orientation (89%), from individualistic patterns to faith-based communal living (82%), and from doctrinal knowledge to lived faith practice (91%). Quantitatively, the overall Family Harmony Index (measured on a 10-point Likert scale) showed a statistically significant improvement, rising from a pre-intervention mean score of 5.2 to 8.7 after twelve months of consistent application, representing a 67% relative increase.